Mapping Potential Foodsheds Using Regionalized Consumer Expenditure Data for Southeastern Minnesota - Jake C. Galzki; David J. Mulla; Erin Meier (Journal of Agriculture, Food Systems, and Community Development, 2017)
The theoretical concept of a foodshed is nearly a century old, while the tools used to model them—computer software coupled with spatial and statistical datasets—are ever-evolving. In a previous study (Galzki, Mulla, & Peters, 2014), foodshed maps have been created in Southeastern Minnesota that display the potential for local food system capacity in the region. Several assumptions were made based on data and software limitations that make the former results quite theoretical; this study attempts to move those results closer to reality by updating, where relevant. We utilized data produced by a model developed at the University of Minnesota to more effectively estimate regional food expenditures to create a representative diet in the region. We used current land-use data along with site-specific crop yields to analyze the potential food capacity of the region. We used optimization software to allocate food supplies to 53 cities in an attempt to feed all residents in the region and minimize food transportation distances. Improvements in software capacities allowed us to incorporate larger datasets, resulting in more detailed maps and statistics that better represent the potential of local foods in the region. The optimization model indicated the region is capable of sustaining its population entirely on locally derived foods. Each resident can be fed on approximately one-third of a hectare (0.85 acre) of land in the region. The average distance a unit of food travels from farm to grocery store was found to be 15.6 km (9.7 miles). Results also show that 90% of the cultivated land remains in surplus after meeting the food demands of the region, minimizing the impacts on the local agroeconomic system. The surplus of pasture land is smaller, but over half the pasture land in the region is in surplus after food needs are met. We explore an alternative land-use scenario that removes environmentally sensitive cropland from cultivation to illustrate the impact conservation efforts may have on a potential local food system. The updated results of this study bolster the evocative effect of mapping foodsheds and provide a more realistic illustration of how the region could sustain itself on locally derived foods.